Computed Tomography-Guided Trans-scapular Coil Localization for Pulmonary Nodules - Zhang, Jian-Hua; Zhou, Shi-Qing; Xia, Feng-Fei; Wang, Tao (The Thoracic and Cardiovascular Surgeon, 2020)
Background The aim of the study is to evaluate the feasibility, safety, and effectiveness of preoperative computed tomography (CT)-guided trans-scapular coil localization (TSCL) of scapula-blocked pulmonary nodules (PNs).Methods Between November 2015 and May 2020, 11 patients underwent preoperative CT-guided TSCL procedures owing to PN occlusion by scapula.Results A 100% technical success rate was achieved for CT-guided TSCL, with one coil being used for each PN. One patient (9.1%) developed pneumothorax. Successful video-assisted thoracoscopic surgery (VATS)-guided wedge resection of these scapula-blocked PNs was conducted in all patients.Conclusion CT-guided TSCL can be simply and safely used to facilitate successful VATS-guided wedge resection of scapula-blocked PNs.
Keywords: localization; trans-scapular; coil; lung nodule